Antibacterial one-step self-etching dental adhesive with silver nanoparticles synthesized in situ. (February 2023) - Wang, Yichun; Ding, Yashuang; Deng, Jie; Nie, Rongrong; Meng, Xiangfeng
Abstract: Objectives: The objective of this study is to value the long-term antibacterial capability and adhesive properties of one-step self-etching dental adhesive containing silver nanoparticles (AgNPs) synthesized in situ. Methods: One-step self-etching adhesives with various weight percentages of silver 2-ethylhezanoate (0%, 0.05%, 0.10%, and 0.20%) were obtained by in-situ synthesis; the sizes and distribution of the AgNPs in resin were observed. The antibacterial effects of dentin-resin specimens were assessed by various test methods after being aged for 1 week to 1 year. The microtensile bond strength (μTBS) and interfacial nanoleakage (NL) were evaluated using extracted human teeth after being aged for 1 day and 1 year. Results: Uniform distribution of AgNPs in resin was observed in all experimental groups, and the average size was 4.71 nm-4.81 nm. All groups containing AgNPs showed significant antibacterial differences from the control group ( P <0.05) over the ageing of 1 year. Although the increase of concentration tended to improve antibacterial activity, significant differences were not observed between the 0.10% and 0.20% groups ( P >0.05). No significant differences were observed between all experimental groups and the control group in μTBS testing and NL testing at 1-day and 1-year time points ( P >0.05). Conclusions: 0.10% AgNPs synthesized in situ might be appropriate to impart a long-term antibacterial ability to the one-step self-etching adhesive, without affecting its adhesive performance. Clinical Significance: This study suggests that in-situ synthesis of AgNPs is an effective method to improve the antibacterial ability of dental adhesives with the potential to inhibit secondary caries.